2006
DOI: 10.1002/mus.20698
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in carpal tunnel syndrome: Comparison with electrophysiological stage and motor unit number estimate

Abstract: The purpose of this study was to document the ultrasonographic measurement differences in median nerve size between patients with carpal tunnel syndrome (CTS) and controls, and to correlate these findings with electrophysiological stage and motor unit number estimation (MUNE), thereby allowing us to test the validity of ultrasound as a diagnostic modality for assessing the severity of CTS. High-resolution sonography and electrophysiological studies were performed on 41 wrists of 27 patients and compared with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 30 publications
5
57
1
2
Order By: Relevance
“…Several authors have studied the value of highfrequency ultrasonography for the diagnosis of CTS. [2][3][4][5][12][13][14][15][16][17][18][19] In addition to contributing to the diagnostic work-up of patients with suspected CTS, sonographic examination allows noninvasive detection of aberrations such as a bifid nerve or a neuroma, inspection of the surrounding soft tissue with a diagnosis of a synovitis or tenosynovitis, and detection of space-occupying masses. In our study, we found clinically relevant pathologies in 3 of 57 surgically treated wrists in the sonographic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied the value of highfrequency ultrasonography for the diagnosis of CTS. [2][3][4][5][12][13][14][15][16][17][18][19] In addition to contributing to the diagnostic work-up of patients with suspected CTS, sonographic examination allows noninvasive detection of aberrations such as a bifid nerve or a neuroma, inspection of the surrounding soft tissue with a diagnosis of a synovitis or tenosynovitis, and detection of space-occupying masses. In our study, we found clinically relevant pathologies in 3 of 57 surgically treated wrists in the sonographic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al26 reported that the swelling of the median nerve at the proximal carpal tunnel was related to the results of nerve conduction study. Bayrak et al27 reported that the motor unit number estimation of the abductor pollicis brevis muscle was negatively correlated with CSA of the median nerve at the proximal and middle segment of carpal tunnel. Padua et al28 reported that a positive correlation exists between CSA-W and the neurophysiological severity of CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography (US) may also be used for the diagnosis. 8,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] There are numerous studies on each particular diagnostic test. Most of the studies accept EMG as the gold standard and attempt to determine the accuracy of other tests in comparison with EMG.…”
mentioning
confidence: 99%